Fatty acid and cholesterol profiles and hypocholesterolemic, atherogenic, and thrombogenic indices of table eggs in the retail market. Issue 1 (December 2015) - Attia, Youssef; Al-Harthi, Mohammed; Korish, Mohamed; Shiboob, Mohamed
Abstract Background Eggs are an important source of food due to its favorable effects on human health derived from the protein, fats, minerals, vitamins and bioactive components. We studied the effects of source of eggs in the retail market on fatty acids, lipid profiles and antioxidant status in eggs. Methods Eggs from four sources named A, B, C, and D in the retail market were collected to determine fatty acid, total lipid, and cholesterol profiles; hypocholesterolemic, atherogenic and thrombotic indices; antioxidant status (e.g., of malondialdehyde); and total antioxidant capacity in the whole edible parts of eggs (albumen + yolk) and egg yolk. Samples were collected four times and pooled over times to represent 5 and 10 samples per source for determinations of fatty acids and determinations of lipid profiles and antioxidant status, respectively. Results Fatty acid, total lipid, and cholesterol profiles; hypocholesterolemic, atherogenic and thrombotic indices; presence of malondialdehyde; and total antioxidant capacity in the whole edible parts of eggs and egg yolk showed significant differences (P ≥ 0.05) among different sources of eggs in retail market. Source D showed higher levels of saturated fatty acids (SFA) and linoleic and monounsaturated fatty acid (MUFA)/polyunsaturated fatty acid (PUFA) ratio but lower levels of MUFA and linolenic, arachidonic, eicosapentaeonic (EPA), decohexaenoic (DHA), and total ω9 fatty acids and lower unsaturated fatty acids (UFA)/SFA ratio. Similar trend was shown in fatty acids profiles of the whole edible parts of eggs. On the other hand, total cholesterol, low density lipoprotein (LDL), LDL/high density lipoprotein (HDL) ratio, and atherogenic and thrombogenic indices and total antioxidant capacity of source D were significantly higher than those of other source, but levels of hypocholesterolemic index, and malondialdehyde levels were lower for source D. Conclusion Eggs in the retail market in Jeddah city, Saudi Arabia, from May to August 2015 showed a different pattern of fatty acid and cholesterol profiles; hypocholesterolemic, atherogenic, and thrombogenic indices; and antioxidant status, which might reflect the nutritional and husbandry practice of laying hens. This can affect the nutritional values of eggs, and hence, customer benefits, suggesting the need for standardization and quality control based on nutrient index values.